Experimental and numerical investigation of tool-part interacions in composites manufacturing - Özsoy, Övül Özgü. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Composite parts may undergo some shape distortions due to the residual stresses generated during the cure cycle. This may cause difficulties in assembling composite structures. This experimental and numerical work is done to investigate shape distortions, and stress distributions built up during manufacturing due to tool-part interaction. In the numerical study, tool-part interaction induced warpage effects are modeled for flat composite strips in three different ways by using a three step finite element analysis procedure. The analysis is based on a number of simplifying assumptions, most of which are reasonable. Vitrification is treated as a point at which the material suddenly changes from the rubbery to glassy state with constant properties in each case. The models developed take into account the observations on the interactions between the tool and the part and between the prepreg layers themselves, and a work has been carried out to investigate the effect of various process parameters and interface properties on the manufacturing distortions of composite parts. Elasticity solutions were made to compare the results of the two finite element models mentioned above. A closed-form analytical model based on the theory of elasticity is implemented to analyze the process-induced stresses and deformations that develop during the cure cycle of a composite flat part. Solutions were obtained for the sticking and sliding boundary conditions. Through tension test, by loading and unloading a single uncured ply, a load displacement data obtained, which is then converted into stress-strain relation. The difference between the loading and unloading curves reveals the initial waviness of fibers. The effect of this behavior on fibre stress development due to tool-part interaction is analyzed. Tool-part investigation is further investigated by marked-tool test. This test is a new method to measure the degree of tool-part interaction. End observations were made through image analysis of the samples cut from the corners of both ends of the specimens under the optical microscope. These experimental observations are tried to be explained by the help of analytical tools developed.
Keywords: Composite materials.; Manufacturing processes.